THE INFLUENCE OF THE INTRINSIC VALUE OF STOCKS ON ITS MARKET PRICE - Kennedy, Posma Sariguna Johnson; Sinaga, Monalisa Kartini (Universitas Pendidikan Indonesia, 2022)
The intrinsic value of a stock does not necessarily reflect its fair market price. This study aims to test whether there is an effect of intrinsic stock value on the formation of its market price, using a sample of stocks listed on the LQ-45 Index in 2018-2019 on the Indonesia Stock Exchange. The research method used is a quantitative method using linear regression analysis. The regression results show that the intrinsic value variable has a significant positive effect on stock market prices listed on the 2018-2019 LQ-45 Stock Index on the Indonesia Stock Exchange.